Interactive voice response technology for telephony system - Abu Shariah, Mohammad A. M.; Ainon, Raja Noor; Khalifa, Othman Omran (IIUM Press, 2011)
Speech is tbe primary means of communication between people. For reasons ranging from technology curiosity about the mechanism for mechanical realization of human speech capabilities. To the desire to automate simple tasks inherently requiring human-machine interactions. There have been many interesting advances and developments since the invention of the first speech recognizer at Bell Labs in the early 1950's. Besides inventing useful automated speech recognizers, scientislS and researchers' contribUlions were to produce emeienl algorilhms lhal help 10 pnxlucc beller quality aulomated speech recognition systems. and improve lhe accuracy and malching standanrd in order to make the syslems more useful